2021
DOI: 10.1038/s41531-021-00241-3
|View full text |Cite
|
Sign up to set email alerts
|

Glucosylceramide in cerebrospinal fluid of patients with GBA-associated and idiopathic Parkinson’s disease enrolled in PPMI

Abstract: Protein-coding variants in the GBA gene modulate susceptibility and progression in ~10% of patients with Parkinson’s disease (PD). GBA encodes the β-glucocerebrosidase enzyme that hydrolyzes glucosylceramide. We hypothesized that GBA mutations will lead to glucosylceramide accumulation in cerebrospinal fluid (CSF). Glucosylceramide, ceramide, sphingomyelin, and lactosylceramide levels were measured by liquid chromatography-tandem mass spectrometry in CSF of 411 participants from the Parkinson’s Progression Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 36 publications
(56 reference statements)
0
24
1
Order By: Relevance
“…Therefore, this methodology should be appropriate for highly heterogeneous diseases, such as PD, where many biological processes intersect to form a slightly different pathology in each individual. [21][22][23][24][25] It should be noted that patients with PD were often subgrouped by the presence or absence of GBA1, LRRK2, and SNCA mutations because these mutations affect the PD phenotype and biomarker profiles, [26][27][28][29][30][31][32] indicating the possibility that proteomic characteristics are also different among these subtypes. With this background, the aim of this study, which measured 4071 human proteins in the CSF of 1149 subjects recruited in the Parkinson's Progression Markers Initiative (PPMI) study, was threefold.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this methodology should be appropriate for highly heterogeneous diseases, such as PD, where many biological processes intersect to form a slightly different pathology in each individual. [21][22][23][24][25] It should be noted that patients with PD were often subgrouped by the presence or absence of GBA1, LRRK2, and SNCA mutations because these mutations affect the PD phenotype and biomarker profiles, [26][27][28][29][30][31][32] indicating the possibility that proteomic characteristics are also different among these subtypes. With this background, the aim of this study, which measured 4071 human proteins in the CSF of 1149 subjects recruited in the Parkinson's Progression Markers Initiative (PPMI) study, was threefold.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies even suggest a prognostic value of lysosomal markers. In the longitudinal observation of the PPMI cohort including GBA-PD and sPD, the glucosylceramide fraction was increased, whereas the sphingomyelin fraction was reduced in the CSF of GBA-PD patients compared to controls [ 73 ]. However, a higher ratio of glucosylceramide to sphingomyelin significantly associated with an accelerated cognitive decline in sPD compared to the sPD subjects with a lower ratio.…”
Section: Lysosomal Biomarkersmentioning
confidence: 99%
“…Mutations in this gene are found in up to 10% of patients with PD, thus implicating aberrant sphingolipid metabolism [ 135 ]. Indeed, the CSF lipidome signatures of Parkinson’s patients at early stages, de novo PD patients with abnormal dopamine transporters, and healthy controls show distinct lipidome changes, with a significant increase in glucosylceramide (GlcCer), while sphingomyelin (SM) was significantly reduced in GBA-PD patients [ 93 ]. Furthermore, applying the ratio of GlcCer to SM for stratifying cases of idiopathic PD revealed that patients with a high GlcCer/SM ratio present increased cognitive deterioration compared to those in the lowest quartiles.…”
Section: Lipids and Parkinson’s Diseasementioning
confidence: 99%